PENGARUH METODE BODY PAINTING TERHADAP PEMAHAMAN ANATOMI OTOT PADA MAHASISWA PENDIDIKAN JASMANI (STUDI PADA MATA KULIAH MASSAGE-FISIOTERAPI CEDERA OLAHRAGA) - Ningrum, Nurul Fajar Muslimah; Afrilliyan, Arrendi; Khairi, Azizatul (YLPK Mahardhika, 2025)
This study aims to determine the effect of the body painting method on the understanding of muscle anatomy in physical education students. This type of research is a quasi-experimental study using a nonequivalent control group design. The subjects of the study were 4th semester students consisting of class A and class B totaling 52 students. The instrument used was a multiple-choice test. The quality test of the test item assessment instrument included validity test, reliability test, question difficulty test, and question discrimination test. The data analysis technique used was a hypothesis test with a t-test to see the difference in understanding of muscle anatomy in the experimental class and the control class with a significance level of 5%. The results of the study showed that there was an effect of the body painting method on understanding muscle anatomy in physical education students. This effect was proven by the results of the t-test on the posttest of the experimental class and the control class obtained tcount ? ttable (2.799> 1.676) with a sig (2 tailed) value of 0.007 <0.05, where tcount is greater than ttable with a sig value less than 0.05.